The Living Church Convictions of a Lifelong Pastor - Stott, John R. W. (England Inter Versity Press, 2007)
Reflecting on his more than sixty years of service at All Souls and a worldwide ministry that led Time magazine to acknowledge him as one of the "100 Most Influential People in the World," Stott alerts a church that is in transition to the marks of a ch
Keywords: Church. Pastoral theology